Implementation Of Collaborative Supervision Program To Improve Teachers' Professional Competence At SD IT AZ-ZAHRA Bojongsari Depok - Agung, Purnomo; Sudin, Mahmudin; Islami, Mita Ulfayanti Nur (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to examine the implementation of a collaborative supervision program to improve teacher professional competence at SDIT Az-Zahra, Bojongsari, Depok. The collaborative approach was chosen because it is considered capable of encouraging active teacher participation and strengthening the quality of learning through supervisory activities that are consultative and evaluative together. The method used is a case study with data collection through observation, interviews, and questionnaires with teachers and supervisors. The results of the study indicate that the implementation of collaborative supervision effectively improves teachers' understanding and skills in designing and implementing innovative learning that is in accordance with the latest pedagogical developments. In addition, this program also encourages a culture of self-evaluation and collaboration among teachers, thereby improving professionalism and the quality of the teaching and learning process in schools. These findings illustrate that collaborative supervision is an effective strategy for teacher professional development and can be widely adopted to improve the quality of education at the elementary level.